Depositional and Diagenetic Controls on Macroscopic Acoustic and Geomechanical Behaviors in Wufeng-Longmaxi Formation Shale - Deng, Jixin; Wang, Chongyi; Zhao, Qun; Guo, Wei; Tang, Genyang; Zhao, Jianguo (Frontiers in Earth Science, 2021)
This integrated study provides significant insight into parameters controlling the dynamic and static elastic behaviors of shale. Acoustic and geomechanical behaviors measurement from laboratory have been coupled with detailed petrographic and geochemical analyses, and microtexture observations on shale samples from the Wufeng−Longmaxi Formation of the southeast Sichuan Basin. The major achievement is the establishment of the link between depositional environment and the subsequent microtexture development, which exerts a critical influence on the elastic properties of the shale samples. Microtexture and compositional variation between upper and lower sections of the Wufeng−Longmaxi Formation show that the former undergoes normal mechanical and chemical compaction to form clay supported matrices with apparent heterogonous mechanical interfaces between rigid clasts and the aligned clay fabric. Samples from lower sections exhibited a microcrystalline quartz-supported matrix with a homogeneous mechanical interface arising from syn-depositional reprecipitation of biogenic quartz cement. This type of microtexture transition exerts primary control on elastic behavior of the shale samples. A clear “V” shaped trend observed from acoustic velocities and static Young’s moduli document contrasting roles played by microtexture, porosity and organic matter in determining elastic properties. Samples with a quartz-supported matrix exhibit elastic deformation and splitting failure modes. Rock brittleness correlates positively with quartz content. This indicates the increment of the continuous biogenic quartz cemented medium with limited mechanic interface. By contrast, samples showing a predominantly clay-supported matrix exhibited more signs of plastic deformation reflecting heterogeneous mechanical interfaces at grain boundaries. Simple increasing the quartz content does not enhance brittleness in clay-supported samples.